2022
DOI: 10.1007/s11846-021-00511-7
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from family firms: the use of flexible work arrangements and its consequences

Abstract: Ongoing trends towards more flexible work arrangements (FWA) have been accelerated by the Covid-19 crisis. Whilst research has shown the overall benefits FWA can have, limited research has explored whether use and benefits of FWA are equal across differentiated organisational contexts and genders. We suggest that individuals working in their family’s business face less organizational constraints that typically hinder employees from taking advantage of FWA. It could be suggested that these workers may make high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Compared to traditional working methods, flexible working approaches offer greater flexibility, sustainability, and convenience and will bring about significant changes. In addition, the COVID-19 outbreak has given impetus to using digital technology for flexible working [1]. Businesses have widely used flexible work arrangements (FWAs) to attract, motivate, and retain critical knowledge-based talent in this context [2].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to traditional working methods, flexible working approaches offer greater flexibility, sustainability, and convenience and will bring about significant changes. In addition, the COVID-19 outbreak has given impetus to using digital technology for flexible working [1]. Businesses have widely used flexible work arrangements (FWAs) to attract, motivate, and retain critical knowledge-based talent in this context [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fotiadis et al (2019) found evidence that family firms, given their emphasis on employee well-being and work-life balance, contribute to decreasing employee burnout. Additionally, family firms often provide more flexible work arrangements, such as telecommuting or adaptable scheduling, enabling employees to balance work and personal responsibilities, thereby alleviating anxiety and pressure that can lead to job burnout during crises ( Stamm et al, 2022 ). The family-like work environment fostered by family firms may also enhance employees’ social adaptability and support, acting as a buffer against the negative effects of stress and burnout during crises ( Schwaiger et al, 2022 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This is because when entrepreneurs leave, it affects their employees, clients, ecosystem stakeholders and family members. This is particularly important in a family business setting (Ahmad and Yaseen, 2018;Ferrari, 2023;Rodriguez-Serna et al, 2022;Stamm et al, 2023). Indeed, the process by which entrepreneurs leave a business, often a family business, is an important part of the entrepreneurial process (Brockhaus, 2004;DeTienne, 2010;Ferrari, 2023;Morris et al, 2020).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…This is particularly important in a family business setting (Ahmad and Yaseen, 2018; Ferrari, 2023; Rodriguez-Serna et al. , 2022; Stamm et al. , 2023).…”
Section: Future Perspectivesmentioning
confidence: 99%